Proses Kreatif Penulis Muslim Indonesia - Nashori, Fuad (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2004)
The purpose of this study is to examine the creative process of Indonesian Muslim writers. The method employed in this study is qualitative method, known as descriptive-explorative. Questions were asked to writers through in-depth interview. These writers have written at least 5 books related to Islam or having Islamic nuances, with concept ranges from Islamic thought/ ideas to fiction. Other than books the participants are actively engaged in writing articles, papers and other forms of writing.The result of this study shows that creative ideas were obtained by:(a)    focusing on one topic, through observing realities related to the topic, and getting involved directly and intensively in activities related to topic of interest.(b)    studying a certain topic by actively engaged in activities to broaden their knowledge related to the topic of interest (e.g., reading, discussion with colleagues, students, spouse, family members, including those who have opposing ideas).(c)    having leisure activities in between their creative engagement (e.g. gardening, sight-seeing).(d)    performing  intensive religious practices (e.g. night prayer, dzikir/supplication).(e)    maintaining good conduct, both thought and behavior, and observing self-control against their own negative feeling (e.g. arrogance, ambition, show-off). These negative psychological states might contaminate their creative process.Keywords: creative process, Muslim writers.